Healthcare Professionals Experience of Psychological Safety, Voice, and Silence - O'Donovan, Róisín; De Brún, Aoife; McAuliffe, Eilish (Frontiers in Psychology, 2021)
Healthcare professionals who feel psychologically safe believe it is safe to take interpersonal risks such as voicing concerns, asking questions and giving feedback. Psychological safety is a complex phenomenon which is influenced by organisational, team and individual level factors. However, it has primarily been assessed as a team-level phenomenon. This study focused on understanding healthcare professionals’ individual experiences of psychological safety. We aim to gain a fuller understanding of the influence team leaders, interpersonal relationships and individual characteristics have on individuals’ psychological safety and their decisions to engage in voice or silence behaviour. Thirty-four interviews were conducted with healthcare professionals from across five teams working within an acute, suburban hospital. Hybrid inductive-deductive thematic analysis focused on identifying themes which captured the complexities of individuals’ varied experiences of psychological safety. The themes identified were: ‘Personal Characteristics’, ‘Past Experiences’, ‘Individual Perceptions of Being Valued’ and ‘Judged Appropriateness of Issues/Concerns’. These themes are explored within the context of motivating and inhibiting factors associated with the influence of leadership, interpersonal relationships and individual characteristics on experiences of psychological safety and voice behaviour. These results extend existing theoretical frameworks guiding our understanding of psychological safety by accounting for the variation in individuals’ experiences and studying these significant influences on voice behaviour. Important considerations for the development of interventions to enhance psychological safety are discussed.